A Suite of Field Manuals for Marine Sampling to Monitor Australian Waters - Przeslawski, Rachel; Foster, Scott; Monk, Jacquomo; Barrett, Neville; Bouchet, Phil; Carroll, Andrew; Langlois, Tim; Lucieer, Vanessa; Williams, Joel; Bax, Nicholas (Frontiers in Marine Science, 2019)
One of the main challenges in assessing marine biodiversity is the lack of consistent approaches to monitor it. This threatens to undermine ocean best practice in marine monitoring, as it impedes a reduction in the bias and variance of sampled data and restricts the confidence in the advice that can be given. In particular, there is potential for confounding between the monitoring methods, their measured ecological properties, and the questions they seek to answer. Australia has developed significant long-term marine monitoring and observing programs and has one of the largest marine estates, including the world’s largest representative network of marine parks. This new network will require ongoing monitoring and evaluation, beyond what direct funding can support, so needs to be integrated in a standardised way with other national programs to develop sufficient monitoring capacity. The aim of this paper is to describe the process undertaken in developing a suite of field manuals that provide standard operating procedures (SOPs) for marine sampling in Australian waters so that data are comparable over time and space, thereby supporting a robust, cost-effective, and objective national monitoring program. We encourage readers to refer to the complete manuals of interest at www.nespmarine.edu.au/field-manuals. Collaboration was a key characteristic of our approach so rather than single groups trying to impose their standards, more than 70 individuals from over 30 organisations contributed to the first version of this field manual package.